Advanced virtual monoenergetic imaging algorithm for lower extremity computed tomography angiography: effects on image quality, artifacts, and peripheral arterial disease evaluation - Jung Han Hwang; Jin Mo Kang; Suyoung Park; So Hyun Park; Jeong Ho Kim; Ki Hyun Lee; Ji Hoon Shin; Seong Yong Pak (Diagnostic and Interventional Radiology, 2023)

(untitled)
PURPOSETo investigate the image quality of lower extremity computed tomography angiography (LE-CTA) using a reconstruction algorithm for monoenergetic images (MEIs) to evaluate peripheral arterial disease (PAD) at different kiloelectron volt (keV) levels.METHODSA total of 146 consecutive patients who underwent LE-CTA on a dual-energy scanner to obtain MEIs at 40, 50, 60, 70, and 80 keV were included. The overall image quality, segmental image quality of the arteries and PAD segments, venous contamination, and metal artifacts from prostheses, which may compromise quality, were analyzed.RESULTSThe mean overall image quality of each MEI was 2.9 ± 0.7, 3.6 ± 0.6, 3.9 ± 0.3, 4.0 ± 0.2, and 4.0 ± 0.2 from 40 to 80 keV, respectively. The segmental image quality gradually increased from 40 to 70–80 keV until reaching its highest value. Among 295 PAD segments in 68 patients, 40 (13.6%) were scored at 1–2 at 40 keV and 13 (4.4%) were scored at 2 at 50 keV, indicating unsatisfactory image quality due to the indistinguishability between high-contrast areas and arterial calcifications. The segments exhibiting metal artifacts and venous contamination were reduced at 70–80 keV (2.6 ± 1.2, 2.7 ± 0.5) compared with at 40 keV (2.4 ± 1.1, 2.5 ± 0.7).CONCLUSIONThe LE-CTA method using a reconstruction algorithm for MEIs at 70–80 keV can enhance the image quality for PAD evaluation and improve mitigate venous contamination and metal artifacts.